2005
DOI: 10.1248/cpb.53.1423
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Citrus Aromatics Nootkatone and Valencene by Microorganisms

Abstract: We are continuing to study the biotransformation of secondary metabolites such as terpenoids and aromatic compounds from crude drugs and liverworts by microorganisms [1][2][3][4][5][6][7] and mammals 8,9) to obtain some functional substances such as pheromones and aromatics. We reported the biotransformation of sesquiterpenoids such as dehydrocostuslactone, costunolide, a-, b-, and g-cyclocostunolides, asantonin, and atractylon from crude drugs, and an amber constituent, (Ϫ)-ambrox by microorganisms such as As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 12 publications
0
56
0
Order By: Relevance
“…
, along with eleven known compounds (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Among them, compounds 2-6, 9, and 11 were isolated from this genus for the first time.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
, along with eleven known compounds (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Among them, compounds 2-6, 9, and 11 were isolated from this genus for the first time.
…”
mentioning
confidence: 99%
“…Furthermore, we recently reported a series of new sesquiterpenes, including seven new eudesmane sesquiterpenes, against NO production from A. oxyphylla [6][7][8]. In continuation of our search for bioactive metabolites from the fruits of A. oxyphylla, we have further isolated 12 eremophilane-type sesquiterpenes, including a new compound, (4R*,5R*)-7-acetyl-4,5-dimethyl-4,5,8,9-tetrahydronaphthalen-2(3H)-one (oxyphyllanone A, 1), along with eleven known sesquiterpenes, (4R*,5S*,7R*)-7-acetyl-4,5-dimethyl-4,5,6,7,8,9-hexahydronaphthalen-2(3H)-one (2) [9], (11R)-nootkatone-11,12-diol (3) [9], (11S)-nootkatone-11,12-diol (4) [9], 11-hydroxyvalenc-1(10)-en-2-one (5) [10], 9E-hydroxynootkatone (6) [9], oxyphyllol B (7) [2], oxyphyllol C (8) [2], epinootkatol (9) [11, 12], nootkatol (10) [12,13], 12-hydroxynootkatone (11) [9,14], and nootkatone (12) [11]. Among them, compounds 2-6, 9, and 11 were isolated from this genus for the first time.…”
mentioning
confidence: 99%
“…[11] All mentioned chemotypes have been described on the basis of chemical data obtained from solvent extracts. [18,[45][46][47] There is only one scientific paper concerning the chemical composition of EOs hydrodistilled from this liverwort species. Warmers and König [48] showed that gymnomitranes and cuparanes are the major components present in EOs obtained from the European specimen, as well as in the solvent extract.…”
Section: Complex Thalloid Liverwortsmentioning
confidence: 99%
“…The biotransformation of the latter by the fungus Aspergillus niger has also been described in this work. 124 A gas chromatographic method has been developed to quantify the chamigrane sesquiterpene elatol, at the surface and within the thallus, of 70 specimens of the red alga Laurencia obtusa. 125 This species also contains the new sesquiterpenes perforenol B 145 and the perforetane derivative 146.…”
Section: Chamigrane Perforane Perforetane and Widdranementioning
confidence: 99%